Analysis results for the effectiveness of monetary policies with fuzzy logic - Dinçer, Hasan; Yüksel, Serhat (IGI Global, 2022)
This chapter aims to examine the effectiveness of central bank policies in E7 economies. For this purpose, five different monetary policy instruments (required reserve ratio, rediscount rate, open market operations, standing facilities, and asset purchase program) are defined as the criteria. On the other side, E7 countries are selected as the alternatives. In the analysis process, fuzzy DEMATEL approach is used to weight the criteria whereas fuzzy TOPSIS and fuzzy VIKOR methods are considered to rank E7 economies. The findings show that open market operations are the most important criterion. However, changing required reserve ratio does not have any powerful impact on the market. Therefore, it is recommended that E7 countries should prefer open market operations instead of required reserve ratio in order to influence the market in an effective manner. Additionally, it is defined that Indonesia has the best performance in the E7 economies while Brazil takes place on the last rank.
Keywords: Monetary Policies; Fuzzy Logic; Analysis Results